Risk Analysis of Operator Work Posture Using the Rapid Entire Body Assessment (REBA) Method in Industrial Machine Production Processes - Naufal Rasyid; Alifah Almas; Hikmal Abrar; Nadila Puspita Tri Handayani; Niken Parwati; Widya Nurcahayanty Tanjung (Metris: Jurnal Sains dan Teknologi, 2026)
In industrial manufacturing environments, non-ergonomic working postures are a major contributing factor to the development of musculoskeletal disorders (MSDs) among machine operators. In spare part production processes, operators are often required to maintain static and awkward postures for prolonged periods, which may increase biomechanical load on the body. This study aims to analyze the risk of operator working postures using the Rapid Entire Body Assessment (REBA) method in an industrial machine spare part production process. The research employed a descriptive observational approach conducted under actual working conditions without modifying existing work methods. Postural data were collected through direct observation and photographic documentation of operators at four main workstations, namely lathe, milling, cylindrical grinding, and surface grinding. Body segment angles, including the neck, trunk, legs, upper arms, lower arms, and wrists, were measured using the APECS application and evaluated using the REBA worksheet. The results indicate that operators at three out of four workstations exhibited forward-bending neck postures, resulting in relatively high neck angle deviations. All analyzed workstations were classified as having a medium level of MSD risk, with REBA scores ranging from 4 to 7. The milling workstation recorded the highest risk level with a REBA score of 7, primarily due to excessive trunk flexion, neck inclination, and prolonged static postures. These findings highlight the need for ergonomic improvements, such as adjusting machine height using platforms or height-adjustable bases, to enable operators to work in a more neutral posture and reduce musculoskeletal risk.